Spiribacter halobius sp. nov., a novel halophilic Gammaproteobacterium with a relatively large genome - Gong, Ya; Ma, Lu; Du, Zhao-Zhong; Zheng, Wei-Shuang; Lu, De-Chen; Du, Zong-Jun (Frontiers in Marine Science, 2022)
Spiribacter is the most abundant bacterial genus in the intermediate-salinity zones of hypersaline environments. However, Spiribacter strains are extremely difficult to isolate in pure culture. Therefore, the characteristics, genome features, and adaption mechanisms that allow Spiribacter strains to thrive in highly saline conditions are largely unknown. Here, we show that Spiribacter is predominant in brines from marine solar salterns and sulfate-type salt lakes with intermediate to saturated salinities. Using a high-salt medium, we isolated a novel strain, Spiribacter halobius E85T, which possesses a relatively large and distinct genome. The genome of strain E85T has a length of 4.17 Mbp, twice that of other Spiribacter species genomes and the largest described genome within the family Ectothiorhodospiraceae. Comparative genomic analyses indicate that approximately 50% of E85T genes are strain-specific, endowing functional differences in its metabolic capabilities, biosynthesis of compatible solutes, and transport and pumping of solutes into the cell from the environment. Hundreds of insertion sequences result in many pseudogenes and frequent gene fragment rearrangements in the E85T genome. Dozens of genomic islands, which show a significant preference for replication, recombination and repair, and cell motility and may have been gained from other bacterial species, are scattered in the genome. This study provides important insights into the general genetic basis for the abundance of Spiribacter in hypersaline environments and the strain-specific genome evolutionary strategies of strain E85T.